2021
DOI: 10.1371/journal.pone.0255222
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal heterogeneity and meteorological factors of hand-foot-and-mouth disease in Xinjiang, China from 2008 to 2016

Abstract: The study aims to depict the temporal and spatial distributions of hand-foot-and-mouth disease (HFMD) in Xinjiang, China and reveal the relationships between the incidence of HFMD and meteorological factors in Xinjiang. With the national surveillance data of HFMD in Xinjiang and meteorological parameters in the study area from 2008 to 2016, in GeoDetector Model, we examined the effects of meteorological factors on the incidence of HFMD in Xinjiang, China, tested the spatial-temporal heterogeneity of HFMD risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…The results www.nature.com/scientificreports/ show that the regression coefficients have different spatial clustering patterns for different seasons. Compared with previous studies [25][26][27] , the AT, ARH, AP and AW factors all have an impact on the number of HFMD cases in Xinjiang. The existing studies have shown that the incidence of HFMD in northern Xinjiang is higher because of its high population density, which is consistent with the results of this study.…”
Section: Discussioncontrasting
confidence: 57%
“…The results www.nature.com/scientificreports/ show that the regression coefficients have different spatial clustering patterns for different seasons. Compared with previous studies [25][26][27] , the AT, ARH, AP and AW factors all have an impact on the number of HFMD cases in Xinjiang. The existing studies have shown that the incidence of HFMD in northern Xinjiang is higher because of its high population density, which is consistent with the results of this study.…”
Section: Discussioncontrasting
confidence: 57%
“…However, there was a difference between the northern and southern incidences of HFMD [ 66 ]; therefore, there was some bias in the prediction of HFMD incidence in our study. Third, HFMD occurs because of several factors, including meteorological [ 11 , 13 , 43 ] and holiday effect factors [ 47 ]. However, in this study, the meteorological and holiday effect factors were excluded from the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Global Moran's I index was used to evaluate global spatial autocorrelation. The Lisa cluster map and Lisa significance map were used to describe local spatial autocorrelation[ 17 , 18 ]. Spearman correlation analysis was performed with R software to explore the effect of GERD on the incidence rate of upper gastrointestinal tumours.…”
Section: Methodsmentioning
confidence: 99%